Proceedings of International Conference on Wireless Communication ICWiCom 2017 (Lecture Notes on Data Engineering and Communications Technologies,, 2018)
The volume comprises best selected papers presented at International Conference on Wireless Communication (ICWiCOM) which is organized by Department of Electronics and Telecommunication Engineering of D J Sanghvi College of Engineering. The volume focusses on narrowed topics of wireless communication like signal and image processing applicable to wireless domain, networking, microwave and antenna designs, tele-medicine systems, etc. The papers are divided into three main domains like, networking, antenna designs and embedded systems applicable to the communication domain. The content will be helpful for Post-Graduate and Doctoral students in their research.h.